DIFFRENCE OF EMOTIONAL INTELLIGENCE AND AGGRESSIONBEHAVIOR BETWEEN CHILDREN WHO HAVE MIGRANT WORKER MOTHER AND CHILDREN WHO LIVE WITH THEIR MOTHER (STUDY IN PRIMARY SCHOOLS IN GABUS SUB REGENCY, PATI REGENCY, CENTRAL JAVA) - Nurul Aeni (Pusbindiklat - LIPI, 2011)
Mother has significant roles on child development. Absence of mother potentially causes children maladap tive behavior like aggression. The objectives of this research: (1) to compare emotional intelligence of children who have migrant worker mother with children who live with their mother; (2) to compare aggression behavior of children who have migrant worker mother with children who live with their mother; (3) to analyze determination of mother’s status to aggression behavior with emotional intelligence as intervening variable. This research uses quantitative method. It uses 80 first primary school students in Gabus Sub regency, Pati Regency who are obtained by class random. Quantitative data are obtained from two psychological scales. Scale of Student Aggression Behavior contains 14 items (α = 0,785) and Scale of emotional intelligence contains 23 item (α = 0,865). This research has three findings: (1) children who have migrant worker mother have lower emotional intelligence than children who live with their mother; (2) children who have migrant worker mother more are aggressive than children who live with their mother; (3) Mother’s status determines children’s aggression behavior with emotional intelligence as intervening variable.